HOLOCENE DYNAMICS OF A RELICT MOSS COMPLEX IN THE KOROTOVSKOE MIRE (STATE COMPLEX «ZAVIDOVO», RUSSIA) - Maria B. Nosova; Elena D. Lapshina; Alexander A. Notov; Mikhail S. Ignatov (Nature Conservation Research: Заповедная наука, 2022)
The Korotovskoe mire in the National Park «State complex “Zavidovo”» is the only mire massif in the Moscow Region (Russia) where the postglacial relict complex of vascular plants (e.g. Betula humilis, Pedicularis sceptrum-carolinum, Saxifraga hirculus, Trichophorum alpinum) and mosses (e.g. Cinclidium stygium, Drepanocladus trifarius, Hamatocaulis vernicosus, Meesia triquetra, Paludella squarrosa, Scorpidium scorpioides, S. cossonii, Tomentypnum nitens) is maximally saved. This complex is typical for spring fens. We studied the main stages of the mire development during the last 10 000 years using the analysis of macroremains and radiocarbon analysis. It was shown that despite the instability of the water regime on the mire, minerotrophic mosses were found in the most peat layers. This fact confirms the stability of mineral water inflow during the early and middle Holocene. Meesia triquetra and Drepanocladus trifarius live on the mire since the Boreal period. During the Atlantic and Subboreal period (when the mire surface dried out) there was a very slow peat deposition and the mire was covered by trees, together with a decrease in minerotrophic mosses in the vegetation cover. Scorpidium cossonii, Hamatocaulis vernicosus and Drepanocladus sendtnerii emerge during peat deposits in the Subboreal period after the water regime restoration and the returning of swamp conditions. In the last 2000 years, the surface of the mire was covered by Sphagnum mosses. During the meso-oligotrophic stage of the mire development, mosses demanding a rich mineralisation remained in other parts of the mire, where conditions of rich mineral nutrition lasted longer. Limiting factors of this moss complex during the early and middle Holocene were light and level of mire waters, whereas, in the late Holocene, it was oligotrophisation of the upper peat layers because of a rapid deposition of organic matter. The complex of relict minerotrophic mosses currently existing on mires in the centre of European Russia can be considered as relicts of the glacial time, and, at the same time, as relicts of spring fens, which were more widespread in the early and middle Holocene and gradually having lost their importance as a result of autogenic succession. The obtained data indicate the great nature conservation value of the Korotovskoe mire massif.